THE CARMINA ASISINATIA IN THE LIGHT OF HELLENISTIC POETRY - Giangrande, Giuseppe (Myrtia, 1997)
In this essay the author examines epigrams 1, 9, 7 and 3 published by M. Guarducci and discusses some controversial passages.